PENGEMBANGAN BUKU AJAR MIKROBIOLOGI TERAPAN BERBASIS MASALAH - Pratiwi, Nanda; Hasruddin, Hasruddin; Harahap, Fauziyah (Universitas Sebelas Maret, 2014)
This study is aimed to develop a textbook of applied microbiology problem based in material industrial microbiology by standard BNSP. Teaching materials in the form of textbook will be to guide students in carrying out learning activities applied microbiology course. The research was conducted in the Graduate Program of UNIMED in January-May 2014, with the development model Thiagarajan (4-D), which consists of three stages: the first stage of defining which includes: initial preliminary final analysis, analysis of student, material analysis, task analysis and specification of learning objectives. The second stage of the design, which consists of: the selection of media, format selection, and initial planning. The third stage is the development, consisting of a lecturer assessment, validation by experts and the design of instructional materials, limited testing, and the final device. The resulting product is a textbook that will be used by third semester student of Biology Education Graduate Program of UNIMED. Teaching materials compiled into a book Industrial Microbiology problem based considered feasible by the validation team. Results matter expert team showed an average of 90.30 % very viable category, and instructional design experts categorized 83.4%. limited test group by microbiology lecturer gets by 91.30% results very appropriate category and 40 students of fourth semester of Biology Education Graduate Program of UNIMED assessed at 83.39 % of applied microbiology textbook problem-based in material industrial microbiology compiled interesting.Â Keywords: Development of teaching, materials, applied microbiology, problem-based